Effectiveness of the Team Quiz Method Assisted by Crossword Media to Improve Student Learning Outcomes - Ummu Aiman; Suryadin Hasyda; I Wayan Lasmawan; I Wayan Kertih (Postgraduate, University of Mataram, 2024)
The aim of this research is to determine the effectiveness of the team quiz method assisted by crossword media on the learning outcomes of elementary school students. The approach used in this research is a quantitative approach with a quasi-experimental method using a post-test only control group design. With a total population of class IV students at the Naikoten I State Elementary School, class IV, 30 students from class A and B. Samples were taken using random sampling. Data collection techniques were obtained from written tests in the form of multiple choices. The data analysis technique uses descriptive analysis and inferential statistics with the help of the SPSS version 22 application. The results of the research show that processing the independent t-test data obtained a sig value of 0.000<0.05, then Ha is accepted and H0 is rejected or in other words there is a significant difference between control and experimental classes in improving student learning outcomes on Norms in My Regional Customs material. Thus, it can be concluded that the effectiveness of the Team Quiz Method Assisted by Crossword Media Improves the Learning Outcomes of Class IV Students on Norms in My Regional Customs at the Naikoten I Public Elementary School, Kupang City.